Export prices, markups, and currency choice after a large appreciation - Daniel Kaufmann; Tobias Renkin (University of Neuchâtel, Institute of Economic Research (IRENE), 2019)
We analyze export price adjustment of Swiss manufacturing firms using a novel data set of matched export, import, and domestic prices. After a large, unexpected, and permanent appreciation of the Swiss franc, export prices set in domestic currency fell less than export prices set in foreign currency. This difference prevails if we control for variation in firms' marginal cost. Through the lens of a structural model, this difference can be traced back to strategic complementarity in price setting for firms pricing in foreign currency. Meanwhile, firms setting prices in domestic currency exhibit no strategic complementarity and follow a constant markup-pricing rule.
Keywords: E3; E5; F3; F4; 330; nominal exchange rate; border prices; currency choice; variable markups; pricing-to-market; price rigidity; exchange rate pass through; exchange rate sensitive factor costs